Neuroprotective effect of Scutellaria baicalensis flavones against global ischemic model in rats - Gaire, Bjakta Prasad; Kim, Young Ock; Jin, Zhen Hua; Park, Juyeon; Choi, Hoyoung; Bu, Youngmin; Kim, Hocheol (Journal of Nepal Pharmaceutical Association, 2015)
Scutellaria baicalensis Georgi (SB) is the medicinal plants mainly used in traditional Chinese medicine. It has been used for the treatment of various chronic inflammatory syndromes including respiratory disease, fever and gastric ulcer in traditional Eastern medicine and its major components; baicalin, baicalein and wogonin; were reported to have various biological effects. The aim of this study was to isolate the neuroprotective flavones from the root of S. baicalensis (SB) by bioactivity-guided fractionation of S. baicalensis methanol extract (SBME). Neuroprotective effect of isolated flavones, namely was studied on global ischemic model in rat by 4-VO. SBME was fractionated with different solvent and resulting fractions were administered at a dose of 25 mg/kg to the rat and potent neuroprotective fractions were sub-fractionated. At a dose of 10 mg/kg, isolated compounds, wogonin, and baicalein inhibited the hippocampal neuronal cell death by 78.6% and 81.0% respectively. Our study suggested that SB and its isolated flavones have potential neuroprotective effect and these findings may be one of the alternative therapies for the management of stroke and other neurodegenerative diseases. DOI: http://dx.doi.org/10.3126/jnpa.v27i1.12144 Journal of Nepal Pharmaceutical Association 2014 Vol.XXVII: 1-8